Diagnostic and prognostic role of NLR in testicular cancer - Shirin Sarejloo; Saghar Babadi; Shokoufeh Khanzadeh; Amirhossein Salimi; Alec Clark; Dinyar Khazaeli; Monireh Khanzadeh; Arshin Ghaedi; Brandon Lucke-Wold (Open Exploration Publishing Inc., 2024)
Background: To summarize the results of available studies for investigating the role of neutrophil to lymphocyte ratio (NLR) in testicular cancer (tCa). Methods: The search was conducted on PubMed, Scopus, and Web of Science up to November 21, 2021. Finally, a total of 31 studies were included in this review. Results: NLR was higher in tCa patients compared to healthy controls and benign testis pathologies, and decreased significantly after orchiectomy. An elevated NLR predicts poor prognosis, advanced stage, presence of nodal or distant metastases, contralateral tumor development, lower time-to-cancer specific death, worse OS, and poorer response to chemotherapy. However, NLR could not differentiate between seminomas and non-seminomatous tCa. Discussion: NLR has a significant diagnostic and prognostic value in tCa.